Effect of dry period length and prepartum fat supplementation on energy balance, uterine health, and production of dairy cows - Melad Ahmed; Amjad Riaz; Nasim Ahmad; Muhammad Naveed ul Haque; Hifz ul Rahman; Muhammad Yaseen; Talha Ashraf; Muhammad Abdullah; Ali Hassan; Ali Husnain (Journal of Dairy Science, 2025)
ABSTRACT: We hypothesized that prepartum supplementation of fat in a short dry period would improve postpartum energy balance (EB) and produce milk comparable to the traditional dry period. The objective was to investigate the effect of dry period length and prepartum fat supplementation on DMI, EB, BCS, milk yield, and uterine health. The experiment was a randomized complete block design. Holstein cows were blocked by parity and previous lactation milk yield on 207 ± 3 d of gestation. The experiment was conducted in batches: in the first batch, cows were assigned randomly to either a traditional 60-d dry period (TDP; n = 14) or a short 30-d dry period (SDP; n = 14); in the second batch, cows were assigned to TDP (n = 08), SDP (n = 09), or SDP with fat supplementation (SDP-F; n = 08). Weekly BW, BCS, and daily DMI were recorded from −21 to 105 d relative to calving. Daily milk yield was measured for 105 d postpartum, and milk components were assessed weekly. The vaginal mucus was collected on d 7, 14, and 21 postpartum to diagnose metritis. The data were analyzed by using the MIXED and GLIMMIX procedures in SAS (version 9.4; SAS/STAT, SAS Institute Inc.), and the statistical models included the fixed effect of treatment, time (day or week), interaction between treatment and time, the effect of batch, and the random effect of block and cow nested within treatment. An interaction in the prepartum intake was observed between treatment and week. Cows in TDP had 1.58 kg/d less DMI in wk −1 than in wk −3 relative to calving. The prepartum reduction in DMI was not observed for SDP and SDP-F treatments. Similarly, cows in TDP had a lower prepartum EB on −1 wk of gestation compared with −3 wk relative to calving, but EB between SDP and SDP-F did not differ. Prepartum BCS tended to be higher in SDP-F than in SDP treatment. Postpartum DMI did not differ among treatments, but TDP cows had a lower EB in early lactation than SDP and SDP-F treatments. Milk yield was affected by the interaction between treatment and week. Cows in SDP produced less milk than those in TDP and SDP-F. Cows in SDP-F had lower milk yield during the first 6 wk of lactation than those in TDP. However, during 7 to 15 wk of lactation, SDP-F cows produced milk comparable to TDP cows. Moreover, the total milk yield for 105 d tended to be higher in SDP-F than in the SDP treatment. The incidence of metritis did not differ, but the vaginal mucus score (VMS) was lower in SDP and SDP-F treatments than in TDP on 21 d postpartum. The improved EB for cows receiving the SDP and SDP-F treatments could be attributed to their reduced milk yield, compared with the TDP treatment. However, cows with the SDP-F treatment tended to produce more milk than the SDP treatment. Cows in SDP and SDP-F treatments had improved VMS on 21 d postpartum than TDP, indicating a faster uterine recovery likely due to improved EB in SDP treatments.